TEACHING HORTATORY EXPOSITION TEXT THROUGH K-W-L (KNOW-WANT-LEARN) - Tri Indah Rezeki (STKIP Budidaya Binjai, 2022)
This study was conducted to find out whether K-W-L (Know-Want-Learn) strategy has significant effect in teaching exposition text. The researcher applied experimental design by using pre-test and post-test in the eleventh-grade students of SMK Negeri 1 Tanjung Pura. The researcher used test as the instrument of collecting data and it was analyzed by using t-test formula. The result of this study was a positive effect of the result that applying K-W-L strategy has significant effect in teaching hortatory exposition. It can be seen from the data analysis; it was found that value of class that was taught by applying K-W-L strategy was higher than those not taught by using K-W-L strategy. In order words, using K-W-L (know-want-learn) strategy had effect on students' hortatory exposition text of the eleventh-grade students of SMK Negeri 1 Tanjung Pura. Key Words: Know-Want-Learn, Reading Comprehension, Hortatory Exposition Text